Literature and ethnicity in the cultural borderlands - Gregorio-Godeo, Eduardo de 1975- (Amsterdam : Rodopi, 2002)
This volume stems from the idea that the notion of borders and borderlines as clear-cut frontiers separating not only political and geographical areas, but also cultural, linguistic and semiotic spaces, does not fully address the complexity of contemporary cultural encounters. Centering on a whole range of literary works from the United States and the Caribbean, the contributors suggest and discuss different theoretical and methodological grounds to address the literary production taking place across the lines in North American and Caribbean culture. The volume represents a pioneering attempt at proposing the concept of the border as a useful paradigm not only for the study of Chicano literature but also for the other American literatures. The works presented in the volume illustrate various aspects and manifestations of the textual border(lands), and explore the double-voiced discourse of border texts by writers like Harriet E. Wilson, Rudolfo Anaya, Toni Morrison, Cormac McCarthy, Louise Erdrich, Helena Viramontes, Paule Marshall and Monica Sone, among others. This book is of interest for scholars and researchers in the field of comparative American studies and ethnic studies.